PROPOSED REGULATION LIMITING SMOKING IN INDOOR AREAS (Tufts Archival Research Center, 2007)
Transcript of New York State Public Health Council meeting on a proposed regualtion limiting smoking in indoor areas. Includes testimony from the Commissioner of Nassau County, the Tobacco Institute, various health advocacy groups, and various business interests. Covers arguments for and against such a regulation.